Single and Multi-Person Face Recognition Using the Enhanced Eigenfaces Method - Romić, Krešimir; Livada, Časlav; Glavaš, Andrija (International Journal of Electrical and Computer Engineering Systems, 2016)
This research studies and analyzes the possibility of single-person and multi-person face detection and recognition. Face detection is performed by the Viola-Jones face detection method and recognition is performed by the Eigenfaces method. Unchanged face detection and recognition methods are explained and tested to their limits. Improvement in face recognition is achieved by observing the flaws of the Eigenfaces method and their enhancement.